Analisis penerimaan pajak bumi dan bangunan-P2 serta pengaruhnya terhadap pendapatan daerah Kabupaten/Kota di Provinsi Jambi - Setiawan, Budi; R, M. Rachmad; Delis, Arman (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to analyze the determinants of PBB-P2 revenue, to determine the effect of PBB-P2 revenue on regional revenue and to formulate strategies for increasing PBB-P2 revenue in Jambi Province. The data used in this study is secondary data with the type of Time series 2014-2018 data and Cross Section 11 districts/cities that come from the Central Statistics Agency and Regency / City BPPRD. This study uses Panel Data Regression Analysis and uses Simple Linear Regression using the E-Views 8.0 tool. The results of this study indicate that PBB-P2 always increases every year. From the results of panel data regression analysis, the results show that investment, economic growth, and taxpayers together have a significant effect on PBB-P2 with an R square value of 0.924, the Prob value (F- statistic) 0,000 and the F-statistic value is 26,556. The effect of investment on PBB-P2 has a positive effect, which means that if investment increases, PBB-P2 will also experience an increase. Economic growth and taxpayers will have a negative effect on PBB-P2 which means that the increase in PBB-P2 will decrease the economic growth and taxpayers.